Transition‐Metal‐Free Synthesis of Fluorinated Nitriles and Diaryl Ketones Through a Selective C–F Bond Functionalization Under Mild Conditions. Issue 3 (12th December 2014) - Yang, Guang‐Hui; Liu, Ming; Li, Na; Wu, Ran; Chen, Xu; Pan, Ling‐Ling; Gao, Shang; Huang, Xing; Wang, Chen; Yu, Chuan‐Ming
Abstract: A highly efficient and simple procedure was developed to synthesize substituted fluorinated nitriles and diaryl ketones under mild conditions from polyfluorobenzenes and phenylacetonitriles. This coupling process was achieved by using a selective C–F bond functionalization without a transition‐metal catalyst. The reactions had good functional group tolerance and provided the products in moderate to excellent yields. Abstract : A highly efficient and simple procedure was developed to synthesize substituted fluorinated nitriles and diaryl ketones under mild conditions from polyfluorobenzenes and phenylacetonitriles. This coupling process proceeded through a selective C–F bond functionalization without the use of a transition‐metal catalyst and afforded the products in moderate to excellent yields.